Relationship of Age and Parity with Preeclampsia in Pregnant Women at Regional Technical Implementation Unit Robatal Public Health Center in 2022 - Ilham Bahtiar (Jurnal KESANS : Kesehatan dan Sains, 2023)
Background: Indonesia's maternal mortality rate is the second highest in Southeast Asia after Laos in 2015. Preeclampsy itself is a direct cause of maternal death with multisystem disorders that usually affect 2% - 5% of pregnant women in Indonesia. Objective: Determine the relationship between maternal age and parity on the incidence of preeclampsia.  Method: What is used in this study is an observational study that is analytical in nature with a cross sectional design or approach. The population in this study is all pregnant women of more than 20 weeks gestation in the Regional Technical Implementation Unit of the Robatal Public Health Centerin 2022, with a total sample of 258 people. Sampling technique using Systematic Random Sampling. The statistical test used is the chi square test. Results: Based on analysis with chi-square test, it was concluded that there was a significant association between age and severe preeclampsia (p=0.031 <0.05) and no significant association between parity and severe preeclampsia (p=0.497>0.05).  Conclusions: Based on analysis with chi-square test, it was concluded that there was a significant association between age and severe preeclampsia and no significant association between parity and severe preeclampsia.